INCREASING AWARENESS AND READERSHIP OF TRIBUN JAWA TENGAH NEWSPAPER AS PROJECT MANAGER - Bimandhika Sunu Wardhana; Djoko Setyabudi, S.Sos, MM (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Tribun Jateng is one of a subsidiary company of the Kompas Gramedia. Tribun Jateng was formerly named Warta Jateng, nonetheless, on April, 29th 2013 it changed it’s name to become Tribun Jateng because the Tribun brand itself is a stronger brand already spreadingout in Indonesia. Three months after the re-named, Tribun Jateng is finally had an online news portal, which is jateng.tribunnews.com. “Spirit Baru Jawa Tengah” is the motto of Tribun Jateng. It’s vision is to become a larger, distributed, and a leading bussiness group of publising media in Central Java. Through the motto and vision, Tribun Jateng is constantly working to increase the awareness and readership from the people of Central Java. According to the preliminary data from Tribun Jateng, awareness and the readership of target objective is relatively low. This is further strengthened with the data survey conducted by writer in the field that it’s awareness and readership about Tribun Jateng is still low among the target the objective. Depart with this fact, the writer finally made two event to help improve awareness and readership stands Tribun Jateng. The first even was Semarang Youth Community (SYC). SYC is an event that dedicated for youth people in Semarang that involved local community and local music performer. The goals of Semarang Youth Community is to increase the awareness and readership among 18 – 25 years old. As the results from Semrang Youth Community is the increase in awareness in young people from, originally 71% up to 91 % and the readership from 52 % to 82 %. Whereas, the event of “Jalan Sehat Tribun Jateng Melangkah bersama Paramex ” is an event held in kabupaten grobogan, earmarked to the community of Grobogan County and the surrounding, was aimed to increase the awareness and readership the community of Grobogan County, considering Tribun Jateng had just re-opened the distribution within this area. The achievement of “Jalan Sehat Tribun Jateng Melangkah bersama Paramex” at Grobogan County is the increase of awareness that start at 44% to 69% and readership from 10% to 25% and also the increasing of oplah from 400 to 500 copies for one day. Project manager’s duty in both the event was to managing license of permission for place and security officials. Arranging the concept of the event, looking for talent, controlling flow of the event, stage manager, and lead communication manager and production manager